Prinsip-Prinsip Sejarah Kebudayaan Islam Dalam Membentuk Karakter dan Pendidikan Islam - Bulan Indah Lazia Amalia; Jihan Mutiara Devi; Farah Aurelia Ramadhani; Aditia Sulistiawan; Afiyatun Kholifah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
Islamic Cultural History is an important field of study in Islamic education that not only discusses historical events but also contains moral, spiritual, and social values that can serve as guidelines in human life. This article aims to examine the principles of Islamic Cultural History and its role in shaping character and Islamic education. The research method employed is library research by collecting data from various sources, including books, scientific journals, articles, and relevant documents. The collected data were analyzed using a qualitative descriptive approach to gain a comprehensive understanding of the values contained in Islamic Cultural History. The findings reveal that the principles of Islamic Cultural History include monotheism (tawhid), exemplary conduct, the development of knowledge, justice, and tolerance. These principles significantly contribute to the formation of students’ character, including religiosity, honesty, discipline, responsibility, and respect for others. Furthermore, the learning of Islamic Cultural History strengthens Islamic identity, instills moral values, and supports the achievement of Islamic educational goals that emphasize a balance between intellectual, spiritual, and social dimensions. Therefore, Islamic Cultural History has strong relevance in developing a generation with noble character and morality based on Islamic values.